Subchronic effects of HgCl2 on cognitive function and central inflammation in type 2 diabetic rats: involvement of BDNF and acetylcholinesterase - Benloughmari, Douae; Bikri, Samir; El Aboubi, Meriam; Yassif, Fatima-Zahra; Aboussaleh, Youssef (Frontiers in Toxicology, 2025)
IntroductionType 2 diabetes mellitus (T2DM) is a major global health concern frequently related with chronic low-grade inflammation and a spectrum of cognitive impairments, including deficits in learning and memory. Mercury chloride (HgCl2), a widespread environmental pollutant, is recognized for its neurotoxic properties and its capacity to trigger inflammatory responses, particularly in patients with metabolic disorders such as T2DM.AimThis study aimed to evaluate the subchronic effects of HgCl2 on cognitive performance and neuroinflammation in a rat model of T2DM, with a particular focus on the roles of BDNF and acetylcholinesterase (AChE).Materials and methodsThe experimental design included four groups: control, HgCl2-treated, diabetic, and diabetic rats treated with HgCl2. T2DM was induced by intraperitoneal injections of streptozotocin (STZ) and nicotinamide (NA). Rats in the HgCl2-exposed groups received an oral dose of 0.375 mg/kg/day for 45 consecutive days. Cognitive performance was assessed using behavioral tests targeting spatial learning, recognition memory, and working memory. Additionally, hippocampal and prefrontal cortex (PFC) levels of TNF-α, IL-6, BDNF, and AChE activity were measured to evaluate neuroinflammatory and neurotoxic responses.ResultsThe findings revealed a significant increase in fasting blood glucose levels in both diabetic and HgCl2-treated diabetic groups compared to controls (P < 0.001). Moreover, HgCl2 administration in diabetic rats led to a more pronounced impairment in cognitive functions compared to untreated diabetic rats (P < 0.05). These deficits were associated with enhanced neuroinflammatory markers (TNF-α and IL-6), decreased AChE activity, and reduced BDNF expression in the PFC and hippocampus (P < 0.05).ConclusionOverall, these results highlight the synergistic impact of hyperglycemia and HgCl2 exposure in exacerbating neuroinflammation and cognitive decline, suggesting a critical interaction between metabolic and environmental neurotoxic factors.